If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -45 = 43 Reorder the terms: -45 + y = 43 Solving -45 + y = 43 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '45' to each side of the equation. -45 + 45 + y = 43 + 45 Combine like terms: -45 + 45 = 0 0 + y = 43 + 45 y = 43 + 45 Combine like terms: 43 + 45 = 88 y = 88 Simplifying y = 88
| 3h=6 | | 12(m-4)=3m-3 | | 1/2d=7 | | 8x-6y=6 | | 9w+3=7g+4 | | -12=-2x+2(22-6x) | | 3x+14y=203 | | n/2.8-4.9=-7.11 | | x-12x+5=-50 | | 4-3/2 | | 2x+5=9x-16 | | d=c-13p | | 45=16+x | | -4(3x+1)+5=13 | | 16x+7=-73 | | (5p+3)(5p+3)=8 | | 16x=-73 | | -64x=-1280 | | -7x-3(5x+12)=-146 | | -64x=1280 | | 7+x-(3+32/8)=3 | | X/18=X/960 | | 5(y-3)=8(y-6) | | 2/3=4/5m | | 5t-5=7+2a | | 36=1y+5y+12 | | 14u+4u-15u-2u=8 | | 6(6x+6)-5=1+6v | | -21/(x^2+3) | | 8w-2(2+w)=25 | | -7x-6(-2x+10)=-115 | | 5(2+5x)=-28+6x |